IT outsourcing in Ukraine - Milinevska, Viktoriia; Kovalova, Olena (My University, 2020)
Globalization and the rapid development of technology dramatically changes the behavior of companies. This means that now you need to fight for the client regardless of the location of the competitor, since his proposal is often just a click away on a mobile device or personal computer. The study identified positive trends in Ukrainian IT outsourcing over the past three years. It has been proven that IT outsourcing, especially in times of crisis, becomes a key stabilizing factor and an important strategic solution for business optimization, by reducing the costs of maintaining its own IT service. The positive developments in the domestic IT outsourcing market should be considered, first of all, increasing attention from the domestic business to IT outsourcing; increase the number of working professionals in the IT sphere; increase of the state order for the training of specialists in this field; the emergence of domestic IT companies able to compete with world leaders in the field of IT technologies for business; formation and development of IT clusters in Ukraine. Глобалізація та швидкий розвиток технологій різко змінює поведінку компаній. Це означає, що зараз вам потрібно боротися за клієнта незалежно від місця розташування конкурента, оскільки його пропозиція часто є лише клацанням миші на мобільному пристрої чи персональному комп’ютері. Дослідження виявило позитивні тенденції в українському ІТ-аутсорсингу за останні три роки. Доведено, що аутсорсинг ІТ, особливо в кризові періоди, стає ключовим стабілізуючим фактором та важливим стратегічним рішенням для оптимізації бізнесу, зменшуючи витрати на підтримку власного ІТ-сервісу. Позитивні зрушення на внутрішньому ринку аутсорсингу ІТ слід враховувати, насамперед, посилення уваги вітчизняного бізнесу до ІТ-аутсорсингу; збільшити кількість працюючих професіоналів у сфері ІТ; збільшення державного замовлення на підготовку фахівців у цій галузі; поява вітчизняних ІТ-компаній, здатних конкурувати зі світовими лідерами в галузі ІТ-технологій для бізнесу; становлення та розвиток ІТ-кластерів в Україні.
Keywords: outsourcing (IT); specialist (IT); аутсорсинг (ІТ); фахівець (ІТ); outsourcing market; ринок аутсорсингу; кафедра ділової іноземної мови та міжнародної комунікації